VALIDITY OF STUDENT WORKSHEET BASED GUIDED DISCOVERY ON ECOSYSTEM MATERIAL TO TRAIN STUDENT SCIENCE LITERACY FOR SENIOR HIGH SCHOOL GRADE 10th - Meri Astutik; Sifak Indana (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2019)
Abstract Science literacy is the ability to understand science, communicate science and apply scientific knowledge in daily life. One topic that suitable to train science literacy is ecosystem, because its related to the environment. In the ecosystem learning process, students worksheet based guided discovery can guide students to find concepts independently and apply concept in daily life. The aim of this research was to describe student worksheet based guided discovery on the topic of ecosystem to train student science literacy for senior high school grade 10th. This research reffered to 4D development model, consist of define, design, develop, and disseminate, exlude the stage of disseminate. The instrument which used in this research was a validation sheet. It was used to determine the assessment of student worksheet in terms of appearance aspect, content aspect, language aspect, relevan with guided discovery models and science literacy. Based on the results of the validation, the score of all aspects was 3.88 with percentage of 97.22%, which indicated that the students worksheet was included in the valid category, so that it could be used in the learning process. Keyword : student worksheet, guided discovery, ecosystem, science literacy, valid.